Moisture transfer models for slabs drying - Akpinar, EK; Dincer, I (Pergamon-Elsevier Science Ltd, 2005)
This paper deals with an experimental and theoretical investigation of drying of moist slabs. Experimental part includes the measurement of the moisture content distributions of eggplant slices with 5 mm thickness and 35 mm diameter during drying at the temperatures of 55 degrees C, 65 degrees C, and 75 degrees C and the velocities of 1.0 and 1.5 m/s, respectively. Four drying models are used to determine drying process parameters (e.g., drying coefficient, lag factor, and half-drying time) and moisture transfer parameters (e.g., moisture diffusivity and moisture transfer coefficient), and to calculate moisture content distributions. The calculated values are then compared with the experimental moisture data during the drying of eggplant slices at different drying air temperatures and flow velocities. An excellent agreement is obtained between the calculations and experimental measurements for the cases considered. Also, the experimental drying times are determined and compared with the ones obtained through four different drying models. The results show that all four models are capable of estimating the drying parameters and moisture content distributions. The experimental drying data and model findings are expected to be useful to drying industry. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: drying; moisture transfer; moisture diffusion; models; slab